On-admission High Neutrophil to Lymphocyte Ratio as Predictor of In-hospital Adverse Cardiac Event in ST-elevation Myocardial Infarction - Anggoro B Hartopo1; Ira Puspitawati; Budi Y Setianto (Acta Medica Indonesiana)
Aim: to investigate the role of neutrophil-to-lymphocyte ratio (NLratio) in predicting in-hospital adverse cardiac events in patients with STEMI. Methods: this was a cohort study on patients with STEMI onset ≤24 hour hospitalised in ICCU. NLratio was calculated as absolute neutrophil count divided with lymphocyte count measured by automated blood cell counter on admission.The outcome was in-hospital adverse cardiac events,which were recorded during follow-up. The cut-off value of NLratio to predict outcome was determined by ROC curve analysis. Univariate and multivariable analysis to assess whether high NLratio was independent predictor for in-hospital adverse events were performed. Results: among165 subjects, in-hospital adverse cardiac events occurred in 49 subjects (29%). The cut-off value of NLratio was 6.2. The univariate analysis showed that NLratio >6.2 had an odd ratio of 3.19 (95% CI 1.55-6.55, p=0.002) to develop in-hospital adverse cardiac events. The multivariate analysis showed that NLratio was an independent predictor of in-hospital adverse cardiac events with an odd ratio of 4.10 (95% CI 1.59-10.54, p=0.003). Conclusion: high on-admission NLratio is an independent predictor for in-hospital adverse cardiac events in patients hospitalised for STEMI.